2020
DOI: 10.21203/rs.3.rs-23584/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predictive values of ANGPTL8 on risk of all-cause mortality in diabetic patients: results from the REACTION Study

Abstract: Background: ANGPTL8, an important regulator of lipid metabolism, is increased in diabetes and is associated with insulin resistance. However, the role of ANGPTL8 in the outcomes of diabetic patients remains unclear. This study aimed to investigate circulating levels of ANGPTL8 in participants with and without diabetes and its potential associations with clinical outcomes in a 5-year cohort study.Methods: Propensity-matched cohorts of subjects with and without diabetes from the Risk Evaluation of Cancers in Chi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Although current studies suggest that ANGPTL8 may be a harmful molecule; that is, elevated baseline ANGPTL8 levels are associated with a higher risk of retinopathy and all-cause mortality in patients with T2DM [20][21][22]. At the same time, inhibition of ANGPTL8 appears to be beneficial, manifested by a decrease in circulating triglycerides [112].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although current studies suggest that ANGPTL8 may be a harmful molecule; that is, elevated baseline ANGPTL8 levels are associated with a higher risk of retinopathy and all-cause mortality in patients with T2DM [20][21][22]. At the same time, inhibition of ANGPTL8 appears to be beneficial, manifested by a decrease in circulating triglycerides [112].…”
Section: Discussionmentioning
confidence: 94%
“…The results of clinical prospective study also showed that the baseline ANGPTL8 level was negatively correlated with the risk of metabolic syndrome, even after multivariable adjustment [19]. Paradoxically, the results of another prospective study showed that the baseline ANGPTL8 level was positively correlated with the risk of retinopathy and all-cause mortality in patients with T2DM [20][21][22]. Similarly, a protein truncation variant (PTV) of ANGPTL8 has been shown to reduce the incidence of coronary artery disease (CAD) in a Finnish population [23], while another study has shown a significant reduction in cardiovascular events in CAD patients with high ANGPTL8 levels [24].…”
Section: Introductionmentioning
confidence: 96%